2017
DOI: 10.1080/10256016.2017.1377704
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and isotopic evidences from groundwater and surface water for understanding of natural contamination in chronic kidney disease of unknown etiology (CKDu) endemic zones in Sri Lanka

Abstract: Chronic kidney disease of unknown etiology (CKDu) is the main health issue in the dry zone of Sri Lanka. Despite many studies carried out, causative factors have not been identified yet clearly. According to the multidisciplinary researches carried out so far, potable water is considered as the main causative factor for CKDu. Hence, the present study was carried out with combined isotopic and chemical methods to understand possible relationships between groundwater; the main drinking water source, and CKDu in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
1
32
0
Order By: Relevance
“…Particularly in the dry zone, evaporative isotopic enrichments of shallow groundwater have been reported by Song et al (1999), Edirisinghe et al (2014), and Edirisinghe et al (2017b). However, groundwater and spring water samples in this study plot along the LMWL, indicating less evaporative isotopic enrichment (Fig.…”
Section: Effects Of Evaporative Enrichmentsupporting
confidence: 38%
See 2 more Smart Citations
“…Particularly in the dry zone, evaporative isotopic enrichments of shallow groundwater have been reported by Song et al (1999), Edirisinghe et al (2014), and Edirisinghe et al (2017b). However, groundwater and spring water samples in this study plot along the LMWL, indicating less evaporative isotopic enrichment (Fig.…”
Section: Effects Of Evaporative Enrichmentsupporting
confidence: 38%
“…The two major cities of Sri Lanka, Colombo (the capital) and Kandy, mostly rely on surface water for public water supply, but some relatively large urban centers also base their water supply on groundwaters (Villholth & Rajasooriyar 2010, Herath & Ratnayake 2007. However, water quality problems such as CKDu (Edirisinghe et al 2017b) and dental fluorosis (Jayawardana et al 2012), caused by drinking groundwater, are on the rise, and access to safe water supplies is becoming an important issue. Thus, a thorough understanding of the hydrological cycles in Sri Lanka is necessary to manage water resources at the regional scale.…”
Section: Study Site 1 Climate and Physical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Analyses of water samples in multiple studies indicated the lack of proposed nephrotoxins in drinking water in both CKDmfo-affected and non-affected regions [8,[68][69][70][71]. Analysed components include HMs (Cd, Pb, As, and Cr), agrochemicals (fertilizers and pesticides), and toxins such as ochratoxin, algae-related toxins, organochlorines, and organophosphates.…”
Section: Mechanisms Initiating Tubular Inflammation and Fibrosis Leadmentioning
confidence: 99%
“…Most people with CKDmfo consume water from household, stagnant shallow wells that are not connected to the underground water table or deep tube wells [6,14]. However, the prevalence of CKDmfo is low among those who consume surface water from dynamic water sources, such as reservoirs, streams, irrigating canals, and natural springs [68,71]. Meanwhile, there is no evidence that well water in Sri Lanka and other CKDmfo-affected countries is contaminated with fertilizers, pesticides, or HMs causing CKDmfo [14,68,[74][75][76].…”
Section: Relationship Of Drinking Water and Ckdmfomentioning
confidence: 99%